Legal Vacuums in the Procedural Code of Ethics Trials of the Indonesian National Police - Dicki Agri Kurniawan; Ade Saptomo (Cognitionis Civitatis et Politicae, 2024)
The procedural Code of Ethics trials of the Indonesian National Police face significant legal vacuums that affect law enforcement and public trust. These gaps arise from unclear and conflicting legal provisions, undermining the legitimacy and internal performance of the police institution. This study aims to examine these legal vacuums and propose strategic solutions for their resolution. Utilizing a qualitative research method with legal and institutional analysis, the research investigates the structural and procedural deficiencies in the ethical trials conducted within the police force. The findings reveal a lack of consistency in regulations, insufficient transparency in trial processes, and weak enforcement mechanisms, leading to diminished accountability and public confidence. To address these issues, the study underscores the need for legislative reform, enhanced transparency, legal education for both police personnel and the public, and strengthening the Ethics Commission’s role. These measures are pivotal in ensuring the effective implementation of the Code of Ethics and rebuilding trust in the institution. In conclusion, addressing legal vacuums and fostering ethical accountability will enhance the integrity and legitimacy of the Indonesian National Police in the public’s eyes.